Price Risk For Coal Liquefaction in Moderate Scale Development - Fidya Varayesi; Fans Namara Nazar (Universitas Islam Riau (UIR) Press, 2019)
According to Talla et al,2017 the Linde Hampson Method can be used to process solid changes into liquid. In this study aims to calculate the Linde Hampson method in the temperature range of the Fischer Tropsch method (LTFT /Low temperature fischer tropsch). The temperatures used for comparison include low temperatures of 200 to 250 oC. Parameters compared from the four type of coal namely lignite, antrachitre, bituminous and subbituminous are tested with projects on a moderate scale of 100 – 1000 tons. Analysis of Price risk is carried out to see the trend of change (increase/decrease) in the price of selling syngas. Price can change because of supply and demand. The main factor that can change price is quantity and quality of heat (HHV) and composition. Development of subbituminous can have higher risk than the antrachite type. Based on the calculation of the standard deviation of the risk values obtained from the four types is 25,3.